해염의 영향을 고려한 빗물의 수질 특성 조사 - 한치복; 이택순; 서규태; 정성진 (한국수처리학회지, 19(6), 2011)
Rain water samples were collected in Yangsan, Geoje and Hapcheon from October(2010) to march(2011) and that was analyzed for pH, heavy metals, ionic composition. The results were revealed that Yangsan, Geoje and Hapcheon each made different pH levels of the acidity 4.7, 4.4, 4.9. The Al concentration was in a range of 0.003-0.033 mg/l (average 0.012 mg/l), Cu concentration was 0.002-0.012 mg/l (average 0.007 mg/l), Mn concentration was 0.004-0.052 mg/l (average 0.026 mg/l), and Fe concentration was 0.001-0.021 mg/l (average 0.011 mg/l). The rain water samples of Yangsan, Geoje, Hapcheon showed respectively that is in high concentration of Ca^2+ at 88.7%, 50.3%, 83.2%. The concentration of Mg^2+ and Na+ in rain water samples of Geoje (Mg^2+ 24.4% and Na+ 20.6%) higher than of Yangsan and Hapcheon. The finding suggested that rainwater from Geoje has highly affected by sea salt. KCI Citation Count: 0